Exploring programme design, evaluation of programme performance and describing the clinical outcomes of a public sector based ARV treatment programme in a semi-rural area in the Western Cape over the past 6 years (2004-2010) - Grobbelaar, Cornelis Johannes (Stellenbosch : University of Stellenbosch, 2015)
Background: A national roll-out of antiretroviral therapy in the public sector was started in 2004, and Paarl was one of the first sites to start these services in the Western Cape. Operational research is required to guide the continuous improvement of such services. This research aimed to describe the characteristics of the treatment cohort started at TC Newman CDC’s ARV clinic in Paarl, to determine the retention in treatment rate and to assess the clinical and virological outcomes. Methods: A retrospective descriptive and observational study was done at the TC Newman ARV clinic in Paarl. All adult HIV positive patients that were started on antiretroviral therapy in the given time period were included. Patient and treatment data had been collected in an electronic database (e-register) and were extracted and analysed. Results: Starters: Out of the 2469 patients that were enrolled for ARV treatment between February 2004 and December 2010, 2254 started locally (the rest transferred in). 64% of them were female (decreasing rate over the years). Strugglers: By June 2011 51.5% of patients were still on ARVs, 6.9% patients had died, 16.7% had been ‘transferred out’and 24.7% were reported as ‘Lost to Follow-up’. 40% of the attrition of the cohort occurred in the first 6 months, 70% in the first 18 months. Stayers: Of the 1172 patients retained after start at TC Newman CDC, 1023 (87.3%) were still on Regime 1 and 149 (12.7%) on Regime 2. Conclusions: The results of this treatment cohort (mortality, treatment retention and regimen durability) equal those in other published treatment cohorts, although very limited comparable data are available. However, the high ‘lost to follow-up’ rate is of concern and needs further investigation. Changes in the programme structure and environment tend to have an immediate effect on initiation numbers of new patients.